Leader's human capital as alternative for relational leadership - Henriques, Paulo Lopes (2022)
The current research attempts to revitalize contingency leadership theory. Instead of focusing on subordinate attributes as a substitute for leadership theory, this study examines leader’s human capital attributes as a leadership contingency variable. This paper offers a fresh perspective to contingency leadership literature by exploring a new set of variables. Addressing leader-member exchange (LMX) rather than the conventional focus on leader’s behaviors, this study examines previously untested contingency variables. Using a matched sample of leaders and employees from Portuguese firms, this study examines leader’s education and leader’s organizational tenure as alternatives for LMX with assessed job performance and organizational citizenship as dependent variables. Testing new independent variables sheds additional light on contingency approaches to leadership; as a result, this paper improves the current state of research on contingency leadership. Results seem to indicate that leader’s education is an alternative for LMX as well as suggesting that the leader’s organizational tenure improves LMX. This paper proposes that research focusing on the substitute for leadership may need to examine a different set of variables to determine the viability of contingency approaches to leadership.